Implications of regional surface ozone increases on visibility degradation in southeast China - Lin, Mang; Chan, Iat-Neng; Chan, Chuen-Yu; Engling, Guenter; Bloss, William (Taylor & Francis Open, 2012)
Long-term visibility (1968–2010) and air pollutant (1984–2010) data records in Hong Kong reveal that the occurrence of reduced visibility (RV, defined as the percentage of hours per month with visibility below 8 km in the absence of rain, fog, mist or relative humidity above 95%) in southeast China has increased significantly in the last four decades. The most pronounced rate of increase was observed after 1990 (nine times higher than that before 1990), when notable increases in surface ozone (O3) levels were simultaneously observed (1.06 µg m−3 per yr). The greatest increases in RV, and in O3, NO2 and SO2 concentrations are coincident in the autumn (1.47, 0.20 and 0.45 µg m−3 per yr respectively), when southeast China is strongly influenced by regional O3 formation and accumulation due to continental outflow of pollution from the east China coast under favourable meteorological conditions. Multiple regression revealed that the RV percentage correlated well (p<0.05) with NO2 and NO x in the 1980s, and with NO2, SO2 and O3 after the 1990s, suggesting that there have been changes in the predominant factors causing visibility degradation. In order to elucidate the reasons for these changes, the results were integrated with data from previous research. Possible impacts of elevated O3 on secondary particle formation and their effects on visibility degradation and aerosol radiative forcing in an oxidant-enhanced southeast China are highlighted. Other factors potentially leading to visibility degradation, such as ship emissions and biomass burning, are also discussed.